La política exterior de Estados Unidos en Asia a la deriva: de Barack Obama a Donald Trump - Murakami, Yusuke (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This article analyzes the foreign policy of the United States in Asia, where a fragile status quo with the presence of the United States was established, after falling a traditional vertical and hierarchical States system in the nineteenth century and going through the vagaries of conflicts and wars in the first half of the twentieth century. The main focus will be given to the administration of Barak Obama that introduced a major change on the issue, as well as the current administration of Donald Trump with the tendency to return to the isolationism of the United States. In the twentieth century the superpower had a diplomatic-strategic policy of committing itself to the «liberal international order» based on liberal representative democracy and the free market economy, and avoiding the emergence of a hegemonic country in Western Europe and Asia. This policy was based on the bipartisan consensus among the political decision-makers of Washington, D.C. that gave greater importance to WesternEurope. The Obama administration changed this diplomatic-strategic line, and gave priorityto Asia, while its optimism and idealism regarding China’s position,  along with other diplomatic-economic considerations, allowed the giant of Asia to take a series of acts that caused the change to the territorial status quo. The new diplomatic-strategic line of Obama did not take root in the United States in the end, and with Trump’s coming to power, United States’ policy in Asia has become more confused and contradictory. Although it has become clear that Trump is not interested in maintaining and promoting the «liberal internationalorder», it is still not known exactly what direction or line the Trump administration will takein relation to the political-strategic agenda of relations with Asia. From Obama to Trump, the policy of the superpower in Asia has been going adrift.

Este artículo analiza la política exterior de Estados Unidos en Asia. En dicha región, luego de caer el tradicional sistema vertical y jerárquico de Estados en el siglo XIX y pasar por vaivenes de conflictos y guerras en la primera mitad del siglo XX, la presencia de Estados Unidos permitió el mantenimiento de un statu quo (aunque ciertamente frágil). Este estudio se enfocará, principalmente, en la administración de Barack Obama que introdujo un cambio significativo en relación a la política de Estados Unidos en Asia, así como en la actual administración de Donald Trump la cual presenta una tendencia de retorno al aislacionismo de Estados Unidos. En efecto, en el siglo XX, la superpotencia desarrolló una política diplomático-estratégica de compromiso con el «orden internacional liberal» basada en la democracia liberal representativa y en la economía de libre mercado, para así evitar la aparición de otro país hegemónico en Europa Occidental o en Asia. Dicha política se basaba en el consenso bipartidario entre los agentes políticos de Washington que daba mayor importancia a Europa Occidental. La  administración de Obama cambió esta línea diplomático-estratégica, y dio prioridad a Asia, pero su optimismo e idealismo con respecto a la posición de China, junto con otras consideraciones diplomático-económicas, le permitieron al gigante asiático tomar una serie de acciones que provocaron el cambio del statu quo territorial en Asia. Al final, la nueva línea diplomático-estratégica de Obama no se arraigó en Estados Unidos, y con la llegada al poder de Trump, la política estadunidense en Asia se ha vuelto más confusa y contradictoria. Aunque ha quedado claro que a Trump no le interesa mantener y promover el «orden internacional liberal», todavía no se sabe exactamente qué dirección o rumbo va a tomar su administracióncon relación a la agenda político-estratégica de las  relaciones con Asia. De Obama a Trump, la política de la superpotencia en Asia ha quedado a la deriva.
United States’ Foreign Policy in Asia Going Adrift: From Barak Obama to Donald Trump
Keywords: Política exterior de Estados Unidos; Orden internacional liberal; Aislacionismo; Sistemas de Estados; Asia; China; Corea del Norte; https://purl.org/pe-repo/ocde/ford#5.09.01